Comparative Design of Direct Drive PM Synchronous Motors in Gearless Elevator Systems - Yetis, Hicret; Boztepeli, Hande; Yasa, Yusuf; Mese, Erkan (IEEE, 2013)
In today's world electrical machines become irreplaceable for human beings to continue daily routines. Due to the features such as high efficiency, high starting torque, and silent working, permanent magnet synchronous motors (PMSM) are becoming more common in many applications. One of these applications is gearless elevator system where PMSM seems to be the best candidate so far. In this paper, comparative design of PMSM for gearless elevator has been investigated. Maxwell 2D Finite element analysis software has been used in this study. With comparative design, the influence of pole count on the machine performance is studied. Also, material consumption, weight and costs of two machines have been compared.
Keywords: pmsm; machine design; direct drive; gearless elevator system; maxwell; Energy & Fuels; Engineering